2018
DOI: 10.1103/physrevd.97.046010
|View full text |Cite
|
Sign up to set email alerts
|

Toward de Sitter space from ten dimensions

Abstract: Using a 10D lift of nonperturbative volume stabilization in type IIB string theory, we study the limitations for obtaining de Sitter vacua. Based on this we find that the simplest Kachru, Kallosh, Linde, and Trivedi vacua with a single Kähler modulus stabilized by a gaugino condensate cannot be uplifted to de Sitter. Rather, the uplift flattens out due to stronger backreaction on the volume modulus than has previously been anticipated, resulting in vacua which are metastable and supersymmetry breaking, but tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
375
4

Year Published

2018
2018
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(390 citation statements)
references
References 98 publications
(213 reference statements)
11
375
4
Order By: Relevance
“…By doing so, one may for instance match the known scalar potential for mobile D 3‐brane moduli that are induced by gaugino condensation. Moreover, the SUSY condition 0=DTWW0+#false⟨λλfalse⟩ can be rediscovered in ten dimensions . To us the evidence is convincing enough to believe that a ten dimensional description of KKLT vacua in the spirit of [] is consistent.…”
Section: The Ten Dimensional Perspectivementioning
confidence: 81%
“…By doing so, one may for instance match the known scalar potential for mobile D 3‐brane moduli that are induced by gaugino condensation. Moreover, the SUSY condition 0=DTWW0+#false⟨λλfalse⟩ can be rediscovered in ten dimensions . To us the evidence is convincing enough to believe that a ten dimensional description of KKLT vacua in the spirit of [] is consistent.…”
Section: The Ten Dimensional Perspectivementioning
confidence: 81%
“…In an effort to have a 10D description of gaugino condensation, ref. [] developed a technique to compute the contribution of the anti‐brane to the scalar potential and found no dS solution. This was understood also from the 4D EFT in terms of the nilpotent superfield X by considering the X dependence of W as: ΔW=Xc+e0.16emW np .It is easy to check that for c=0 and e0 the contribution of X to the scalar potential is such that there is no dS vacuum either in KKLT or in LVS…”
Section: De Sitter In String Theorymentioning
confidence: 99%
“…Also in the absence of non‐perturbative effects it is known that c0. Furthermore the analysis in [] does not include the case of Euclidean D3‐instanton contributions to the scalar potential. The proposal presented in [] to obtain dS by considering a racetrack scenario, while possible, has not been implemented in concrete models and may be difficult to construct without fine‐tuning coefficients of the non‐perturbative terms.…”
Section: De Sitter In String Theorymentioning
confidence: 99%
“…This proof does not directly apply to time dependent backgrounds, or to the LVS stabilization mechanism we use, and therefore it presents no immediate obstacle to our model. However, by showing that, in the case of a single Kähler modulus, the antibrane uplift does not simply add to the Kähler moduli potential, [20] invites serious reservations as to the accuracy of all de Sitter constructions using antibranes. A better understanding of the positive energy added by antibranes in time dependent backgrounds with multiple Kähler moduli would certainly benefit the string cosmology community and be extremely relevant to this model.…”
Section: Jhep05(2018)075mentioning
confidence: 99%
“…Finally, it is necessary to mention some important caveats to this work, and the construction of positive vacuum energy solutions in string theory in general. First, recent work [20] has shown that the antibrane uplift in the KKLT [21] construction of de Sitter vacua with a single Kähler modulus is not sufficient to achieve positive vacuum energy. This proof does not directly apply to time dependent backgrounds, or to the LVS stabilization mechanism we use, and therefore it presents no immediate obstacle to our model.…”
Section: Jhep05(2018)075mentioning
confidence: 99%